Aggregate job creation, job destruction and job turnover in the Irish manufacturing sector - Strobl, Eric A.; Walsh, Patrick Paul; Barry, Frank (Economic & Social Studies, 1998)
Using an annual employment survey data set we construct aggregate job flow rates for the Irish manufacturing sector for the period 1974 to 1994. We report the existence of simultaneous job creation and job destruction, inducing job turnover well above that necessary to accommodate net employment changes at the aggregate or even very refined sectoral level, over the entire sample period. This job turnover is caused by a large proportion of the total plant population making mostly persistent adjustments to its employment level. The properties of the aggregate job flows in the Irish manufacturing sector conform well to the stylised facts derived from studies of aggregate job flows in the manufacturing sectors of other developed countries. Moreover, these properties hold regardless of whether we restrict our sample to continuing plants or entering and exiting plants.
Keywords: Employment patterns; Manufacturing sector; Ireland; Job creation; Job losses; Labour market